2011
DOI: 10.1371/journal.pone.0028329
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Functions of the Transketolase Enzyme Isoforms in Rhodopseudomonas palustris Using a Systems Biology Approach

Abstract: Background Rhodopseudomonas palustris (R. palustris) is a purple non-sulfur anoxygenic phototrophic bacterium that belongs to the class of proteobacteria. It is capable of absorbing atmospheric carbon dioxide and converting it to biomass via the process of photosynthesis and the Calvin–Benson–Bassham (CBB) cycle. Transketolase is a key enzyme involved in the CBB cycle. Here, we reveal the functions of transketolase isoforms I and II in R. palustris using a systems biology approach.Methodology/Principal Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…This shunt permits cells a flexible adaptation to different metabolic needs as the pentose phosphate pathway produces nicotinamide adenine dinucleotide phosphate (NADPH) for reductive biosynthetic pathways of cholesterol and fatty acids [60]. Furthermore, a previous study showed that TKT had the potential importance and functional involvement in Rhodopseudomonas palustris growth [61]. S-(hydroxymethyl) glutathione dehydrogenase is involved in NO metabolism that plays crucial roles in defense responses during host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This shunt permits cells a flexible adaptation to different metabolic needs as the pentose phosphate pathway produces nicotinamide adenine dinucleotide phosphate (NADPH) for reductive biosynthetic pathways of cholesterol and fatty acids [60]. Furthermore, a previous study showed that TKT had the potential importance and functional involvement in Rhodopseudomonas palustris growth [61]. S-(hydroxymethyl) glutathione dehydrogenase is involved in NO metabolism that plays crucial roles in defense responses during host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It could convert sunlight to energy and absorb atmospheric carbon dioxide and convert it to biomass (Hu et al 2011). Moreover, it harbors various functions including excretion of plant hormones, N-fixation, and solubilization of mineral nutrients (Kantachote et al 2005;Oda et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoenolpyruvate carboxykinase (PEPCK) activity was determined by measuring ATP formation at 30°C using the Sigma Diagnostics ATP kit (Sigma) as previously described . The PEPCK activity was expressed as amount of ATP (nmole) produced per mg protein per min.…”
Section: Methodsmentioning
confidence: 99%